Torrefaction of durian peel in air and N2 atmospheres: Impact on chemical properties and optimization of energy yield using multilevel factorial design - Jindarat Pimsamarn; Napat Kaewtrakulchai; Awat Wisetsai; Jomthong Mualchontham; Nattawut Muidaeng; Poraphat Jiraphothikul; Chaowat Autthanit; Apiluck Eiad‐ua; Navadol Laosiripojana; Supachai Jadsadajerm (Results in Engineering, 2024)
This study investigated the torrefaction of durian peel using air and nitrogen as carrier gases. A multilevel factorial design coupled with response surface methodology (RSM) and ANOVA analysis was employed to analyze the impact of torrefaction parameters on chemical properties and energy yield. Durian peel, an agricultural waste product, was torrefied at temperatures ranging from 200 to 320 °C for residence times between 0 and 30 min. Results showed that air torrefaction significantly enhanced thermal decomposition, reducing mass yield from 94.65 % to 30.63 % as the temperature increased from 200 °C to 300 °C with a 30-min holding time. Air torrefaction also increased the higher heating value (HHV) from 19.02 MJ/kg to 35.26 MJ/kg at 300 °C, compared to nitrogen, which achieved a maximum HHV of 32.49 MJ/kg. ANOVA analysis revealed that torrefaction temperature and carrier gas significantly affect energy yield and chemical properties. Air torrefaction positively affected HHV while reducing mass yield compared to nitrogen. Low-temperature air torrefaction showed enhanced energy yield improvement. These findings provided insights for optimizing torrefaction processes enhancing utilization wasted durian peel as a sustainable bioenergy resource.
Keywords: Thermochemical Biomass Conversion Processes; Natural Fiber Reinforced Composites; Lignin and Wood Chemistry